Tourism Industry in Uzbekistan: Problems and Development Trends - o’g’li, Axrorov Damir Aslam (International Journal on Integrated Education, 2023)
The cultural and historical artifacts of Uzbekistan are numerous and are regarded as works of global civilizational heritage. Travel and tourism are considered to be the world's top two export industries since they both encourage the growth of the nation's infrastructure, have a good impact on the economy, promote local culture, and help diversify it.